Design and Development Information System Of Inventory Web Based At Depo Galvalum - Putra, Yogie Hartanto; Ayuningtyas, Ayuningtyas; Arrosyidi, Achmad (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Depo Galvalum is a company that moves in galvalum distributor .The process of business on purchase system done by Depo Galvalum still based on Information stock availability . The buying system goods less could be handled well because there is no recording. Sales system just do recording of daily transactions . Recording producing such the total revenues and the amount of goods sold out. The results of recording have not been able to provide information the to conduct an evaluation on a system sales. Leader have only information to the number of goods that have been sold and the rest of the goods. From the report leaders will check repeated that takes time long enough, This leader find it difficult to analyze reports sales still in the form of rekap sales.With the this problem then required inventory information system of goods on Depo Galvalum web-based equipped with reorder point to buy goods next. Of the analysis and design of which is done to provide information on sourcing , an inventory of goods , sale of goods , and preparing reports. The design process produce information system an inventory of goods to suit the needs of Depo Galvalum. These information systems help the Depo Galvalum in the process of purchase of goods , an inventory of goods , sale of goods , and preparing reports.Kata Kunci: information system, inventory , Depo Galvalum , reorder point.